Colorful effect ceramic tile and preparation method thereof

By using a combination of colorful dry particles and transparent dry particles with specific ratios and particle size designs, combined with a system of double-layer protective glaze layer and transparent dry particle layer, the problem of poor matching between colorful dry particles and transparent glaze layer in existing ceramic tiles is solved, and better anti-fouling performance, three-dimensional sense and gloss effect are achieved.

CN119490303BActive Publication Date: 2025-04-01GUANGDONG NEWPEARL CERAMIC GRP CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510085486.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-01
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

The existing flash effect ceramic tiles have poor matching of high melting point colorful dry particles and transparent glaze layer, resulting in defects such as pores, glaze collapse, cracks, and insufficient three-dimensional sense of flash, insufficient wear resistance and insufficient anti-fouling performance.

Method used

The high-melting point characteristic colorful dry particles with specific proportional composition and differentiated particle size design are combined with transparent dry particles. The transparent dry particles are melted into the glass phase first, while the colorful dry particles maintain the integrity of the particles. The transparent dry particles are filled in the gaps between the colorful dry particles, forming a specific system of double-layer protective glaze layer and transparent dry particle layer.

Benefits of technology

It effectively reduces the problem of pore glaze bubbles, improves the anti-fouling performance, enhances the three-dimensional sense and gloss effect, and solves the problem of poor anti-fouling performance caused by dense colorful dry particles and high temperature non-melting in the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490303B_ABST
    Figure CN119490303B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of ceramic tiles, and specifically discloses a colorful ceramic tile and a preparation method thereof. The colorful ceramic tile includes a body layer, a surface glaze layer, a pattern layer, a dry particle mixture layer, a first protective glaze layer, a transparent dry particle layer, and a second protective glaze layer from bottom to top; the dry particle mixture layer is formed by a dry particle mixture, and the dry particle mixture includes colorful dry particles and transparent dry particles with a mass ratio of 1: (0.55-0.65) with differentiated particle sizes; the protective glaze layer includes glue and a slurry of protective glaze containing oxides with a similar composition to the transparent dry particles and a relatively smaller particle size. The ceramic tile prepared by the present invention has a three-dimensional suspended colorful effect, and has a smooth surface, strong transparency, good anti-fouling and wear resistance, which can meet the personalized aesthetic needs of consumers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic tiles, and in particular relates to a colorful effect ceramic tile and a preparation method thereof. Background Art

[0002] As people's living standards continue to improve, their requirements for home decoration are gradually developing in the direction of personalization, and their requirements for the surface texture and decorativeness of ceramic tile products are also getting higher and higher. Therefore, in order to meet the various needs of consumers, various new materials, new formulas, and new processes are constantly being used. Among them, various "dry particles" such as transparent, colorful, glittering, and crystallized are used more and more as raw material carriers in ceramic tiles. Under the irradiation of light, these dry particles can make the surface of ceramic tiles achieve starlight and / or dazzling and colorful effects.

[0003] At present, the crystallized dry particles and flash dry particles are basically made of zircon sand to achieve the flash effect. However, due to the high melting point and refractory characteristics of zircon sand dry particles and the matching problem of transparent glaze layer, defects such as pores, glaze collapse, and cracks are easily generated around the zircon sand dry particles. In addition, there are also problems such as insufficient flash three-dimensional sense, insufficient wear resistance and insufficient anti-fouling performance. Therefore, the existing flash effect ceramic tile technology still has certain limitations. Summary of the invention

[0004] The purpose of the present invention is to solve the deficiencies of the prior art. Based on this, the first aspect of the present invention provides a colorful effect ceramic tile, which includes, from bottom to top, a body layer, a glaze layer, a pattern layer, a dry particle mixture layer, a first protective glaze layer, a transparent dry particle layer, and a second protective glaze layer;

[0005] The dry granule mixture layer is formed by a dry granule mixture, and the dry granule mixture includes colorful dry granules and transparent dry granules in a mass ratio of 1:(0.55-0.65); the D97 of the colorful dry granules is 250 µm-300 µm, and the D97 of the transparent dry granules is 125 µm-150 µm;

[0006] The colorful dry particles include, by mass percentage: SiO2 31.0%-35.0%, ZrO2 65.0%-69.0%;

[0007] The transparent dry particles include, by mass percentage, SiO2 53.0%-60.0%, Al2O3 7.2%-8.4%, CaO 11.5%-13.5%, K2O 5.3%-6.3%, Na2O 2.2%-2.8%, ZnO 13.5%-15.5%, and the rest are loss on ignition and impurities;

[0008] The transparent dry particle layer is formed by the transparent dry particles;

[0009] The first protective glaze layer and the second protective glaze layer are both formed by a first mixture, the first mixture includes a first glue and a slurry, the slurry includes a protective glaze; the D97 of the protective glaze is 21 µm-25 µm; the protective glaze includes, by mass percentage: SiO2 53.3%-60.0%, Al2O3 12.5%-15.3%, CaO 9.0%-11.4%, K2O 5.0%-6.2%, Na2O 1.4%-2.0%, ZnO 3.4%-4.2%, and the rest are loss on ignition and impurities.

[0010] The present invention adopts a combination of high-melting-point characteristic colorful dry particles and low-melting-point characteristic transparent dry particles with a specific ratio composition and differentiated particle size design, so that during the firing process, the transparent dry particles can be first melted into a glass phase, while the colorful dry particles can maintain the integrity of the particles, and the transparent dry particles with finer particle sizes can effectively fill the gaps between the colorful dry particles after melting, thereby effectively reducing the problem of pores and glaze bubbles caused by a large number of stacking gaps caused by the direct stacking of colorful dry particles if a single colorful dry particle is used, and solves the problem of poor anti-fouling performance caused by the dense colorful dry particles and non-melting at high temperatures if a single colorful dry particle is used.

[0011] Among them, the transparent dry particles contain a relatively high content of sodium oxide (2.2%-2.8%), which can greatly enhance the melting property and thus significantly reduce the initial melting temperature and melting temperature, so that the transparent dry particles melt quickly and have the characteristics of low viscosity. The low viscosity enables the molten liquid phase to better occupy the stacking gaps that wrap the colorful dry particles, which is more conducive to the complete wrapping of the colorful dry particles by the transparent dry particles, avoiding the formation of bubble defects and poor anti-fouling performance; at the same time, the high potassium component (5.3%-6.3%) can effectively eliminate the influence of the low-temperature rapid melting of sodium oxide on the narrow melting range, broaden the firing range, reduce the surface tension of the molten glass, and is conducive to the removal of bubbles, and can also improve the adverse effects of the acidic oxide of silica, improve the overall acid and alkali resistance, and the potassium-oxygen ion bond strength is relatively weak, which can effectively inhibit crystallization and phase separation, thereby maintaining the permeability of the dry particle mixture layer and the transparent dry particle layer; in addition, the packaging The high calcium content (11.5%-13.5%) can effectively reduce the eutectic point, promote sintering, increase the density of the glass body and further improve the anti-fouling performance, and strengthen the glass structure, thereby improving the mechanical strength of the glass phase and the durability of acid and alkali resistance, and having better stability in the layer; and the high content of zinc oxide (13.5%-15.5%) can reduce the thermal expansion coefficient of the glass phase, effectively offset the adverse effects of high expansion caused by sodium and potassium, improve its thermal stability and chemical stability and refractive index, increase the gloss of the glass phase and effectively reduce the viscosity at the same time, and also help to remove bubbles in the layer, and have a good clarification effect; the high content of silica can form more silica glass, which makes the light transmittance higher. At the same time, the high silicon-aluminum ratio can make the activation ability of crystallization lower, and it is not easy to precipitate crystals, thereby making the overall transparency higher, and the color effect of colorful dry particles and patterns better.

[0012] In addition, during the dry application process, the colorful dry granule mixture is tumbling and rolling, and the transparent dry granules are more likely to settle in the bottom gap due to their relatively small particle size. At the same time, the smaller kinetic energy they generate makes them less active and easier to adhere to the lower layer. Therefore, they can effectively support the colorful dry granules and fill them between the colorful dry granules. Combined with the low temperature / low melting point characteristics of the transparent dry granules, the colorful dry granules can be better independently "suspended" to form a more three-dimensional particle shape. The colorful dry particles used in the present invention have a higher refractive index and reflectivity, and can form an irregular grain state. The irregular surfaces can reflect and refract external light at different angles, so that the ability of light to reflect light inside the grains is enhanced. Because the shapes of the colorful dry particles are different, each colorful dry particle is an irregular polyhedron, which can disperse the light, decompose the complex light into monochromatic light, and refract it at the bottom, side and other visual angles to form a variety of colors, which are then interwoven with the surface reflected light to form a colorful effect. The suspended colorful dry particles can fully present the colorful effect. Therefore, the ceramic tiles prepared by the present invention can see the three-dimensional suspended visual colorful effect of the colorful dry particles at different angles under light irradiation, and due to multiple reflections and refractions, each surface of the colorful dry particles presents a variety of different luster flashes, which solves the problem that the grain effect of the prior art in imitating high-end stone is not realistic enough, and can bring new visual perception and higher-end use enjoyment to consumers.

[0013] On the basis of the above, the present invention further arranges a protective glaze + glue (i.e. the first glue mentioned above, which can be a conventional commercially available product) of a specific ratio on the dry particle mixture layer as a double-layer protective glaze layer and a transparent dry particle layer arranged therebetween, wherein the use of liquid glaze slurry and the introduction of glue can enable the protective glaze slurry to penetrate into the dry particle mixture layer and the transparent dry particle layer more quickly during the application process and form a coupling effect on the dry particle mixture and the transparent dry particles, thereby protecting the pattern (with good coloring effect) and during the firing process, the multiple layers of protective glaze melt with the transparent dry particles, further protecting the colorful dry particles, thereby making the dry particle mixture layer and the transparent dry particle layer full of glass phase bring a more transparent presentation effect to the entire board surface. The oxide components in the protective glaze used in the present invention are relatively close to the components of the transparent dry particles, and are combined with a relatively smaller particle size (D97 is 21 µm-25 µm), which can further promote the low-temperature eutectic melting of the dry particle mixture layer, ensuring permeability while not affecting the color development of the bottom pattern and the colorful dry particle effect; and the relatively smaller particle size can form a denser contact layer between the dry particle mixture and the inkjet pattern (pattern layer), further avoiding the formation of ink dots in the gaps where the colorful dry particles with relatively coarse particle sizes (D97 is 250 µm-300 µm) in the dry particle mixture are directly combined with the inkjet pattern, thereby affecting the pattern effect. At the same time, since the protective glaze has a finer particle size, it will quickly penetrate into the gaps in the transparent dry particles and form a surface bonding layer together with the transparent dry particles in the transparent dry particle layer, so that the surface of the ceramic tile obtained after firing has a high transparency (clearly presenting the three-dimensional suspended colorful effect of the colorful dry particles) and a good anti-fouling effect. In addition, the introduced calcite can effectively lower the firing temperature and viscosity, making the reaction smoother and reducing the generation of bubbles, thereby improving the surface smoothness and anti-fouling performance. At the same time, the higher aluminum oxide content in the protective glaze can effectively improve the wear resistance and hardness of the transparent dry particle layer, as well as the appropriate amount of zinc oxide, which improves the color of the ink and makes the pattern richer. At the same time, it is combined with a high content of calcium oxide to further promote sintering, improve density and anti-fouling performance.

[0014] In addition, using the same transparent dry particles in the transparent dry particle layer and the mixed dry particle layer can ensure that there are no more different types of oxide reactions, the melting temperature is the same and the reaction is consistent during the process, which can reduce the intensity of the reaction, is beneficial to the density of each layer and the elimination of bubbles and prickly heat, and has better permeability.

[0015] Among them, from the surface of the above-mentioned ceramic tile products, the above-mentioned colorful dry particles are evenly or randomly distributed, occupying 5%-30% of the surface area; and / or, the above-mentioned colorful dry particles are distributed in preset positions and occupy 50%-80% of the surface area in the preset positions. That is, the presentation (distribution) method of the above-mentioned colorful dry particles on the surface of the colorful effect ceramic tiles includes method one, method two, method three, method four or method five; method one is: the above-mentioned colorful dry particles are evenly or randomly distributed on the surface of the above-mentioned colorful effect ceramic tiles, and the above-mentioned colorful dry particles occupy 5%-30% of the surface area of ​​the above-mentioned colorful effect ceramic tiles; method two is: the above-mentioned colorful dry particles are distributed in preset positions on the surface of the above-mentioned colorful effect ceramic tiles, and occupy 50%-80% of the area in the preset positions; methods three, four and five are : The surface of the colorful effect ceramic tile includes a first area (preset position) and a second area (a non-preset position or an area other than the preset position). The colorful dry particles are distributed in the first area (preset position) and occupy 50%-80% of the area in the first area (preset position). At the same time, the colorful dry particles are evenly distributed or randomly distributed in the second area (a non-preset position or an area other than the preset position) and occupy 5%-30% of the area of ​​the second area (a non-preset position or an area other than the preset position).

[0016] The raw materials of the transparent dry particles include, by weight: 21-25 parts of albite, 25.5-30.5 parts of quartz, 14-17 parts of calcite, 9-11 parts of wollastonite, 13-16 parts of zinc oxide, 2.5-3.5 parts of aluminum oxide, and 5.5-6.5 parts of potassium nitrate. The preparation method of the transparent dry particles includes the following steps: mixing the raw materials of the transparent dry particles, calcining and melting (the temperature can be 1400°C), cooling (the molten glass can be rapidly cooled by a water bath or a water-cooled metal roller), and then crushing to obtain the transparent dry particles.

[0017] The raw materials of the protective glaze include, by weight, 42-50 parts of potassium feldspar, 16-20 parts of quartz, 14.5-17.5 parts of wollastonite, 9-11 parts of calcite, 6-8 parts of aluminum oxide, and 2.5-3.5 parts of zinc oxide. The preparation method of the slurry includes the following steps: mixing the raw materials of the protective glaze, water, a thickener (commonly available products such as methyl cellulose) and a dispersant (commonly available products such as sodium tripolyphosphate) and obtaining the slurry through ball milling, sieving and aging.

[0018] The second aspect of the present invention provides a method for preparing the above-mentioned colorful effect ceramic tile, comprising the following steps:

[0019] Applying a slurry containing a glaze on the surface of the green body layer, followed by spraying and applying, then spraying the first mixture for the first time, then applying the transparent dry particles, and then spraying the first mixture for the second time; firing to obtain the colorful ceramic tile;

[0020] The specific process of the printing and application treatment includes scheme 1, scheme 2, scheme 3, scheme 4 or scheme 5; the scheme 1 includes the following steps: printing a pattern to form the pattern layer, and then applying the dry granular mixture, the application amount of which is 20 g / m 2 -120 g / m 2 ;

[0021] The second scheme comprises the following steps: printing a pattern to form the pattern layer, printing a positioning glue on the surface of the pattern layer according to a preset position, and then applying the dry granular mixture, and then removing the excess dry granular mixture that is not attached to the positioning glue, and the application amount is 200 g / m 2 -320 g / m 2 ;

[0022] The third scheme comprises the following steps: printing a pattern to form the pattern layer, printing positioning glue on the surface of the pattern layer according to a preset position, and then applying the dry granular mixture for the first time, with an application amount of 200 g / m 2 -320 g / m 2 Then, the excess dry granular mixture that is not attached to the positioning glue is removed, and then the dry granular mixture is applied for the second time, with an application amount of 20 g / m 2 -120 g / m 2 ;

[0023] The fourth scheme comprises the following steps: printing a pattern to form the pattern layer, printing positioning glue on the surface of the pattern layer according to a preset position, and then applying the dry granular mixture for the first time, with an application amount of 200 g / m 2 -320 g / m 2 Then, the excess dry granular mixture that is not adhered to the positioning glue is removed, and then the positioning glue is sprayed at a non-preset position, and then the dry granular mixture is applied for the second time, with an application amount of 20 g / m 2 -120 g / m 2 , and then removing the excess dry granular mixture that is not adhered to the positioning glue;

[0024] The fifth scheme comprises the following steps: printing a pattern to form the pattern layer, printing positioning glue on the surface of the pattern layer to cover the pattern layer, and applying the dry granular mixture at a preset position in an amount of 200 g / m 2 -320 g / m2 Then the dry granular mixture is applied again at an application rate of 20 g / m 2 -120 g / m 2 , and then remove the excess dry granular mixture that is not adhered to the preset position.

[0025] When sprayed for the first time, the specific gravity of the first mixture is 1.09 g / cm 3 -1.11 g / cm 3 , spraying rate is 265 g / m 2 -285 g / m 2 ; Wherein, the specific gravity of the prepared slurry is 1.88 g / cm 3 -1.92 g / cm 3 , and then adding the first glue to obtain the first mixture with the above specific gravity.

[0026] During the second spraying, the specific gravity of the first mixture was 1.07 g / cm 3 -1.09 g / cm 3 , spraying rate is 175 g / m 2 -195 g / m 2 ; Wherein, the specific gravity of the prepared slurry is 1.88 g / cm 3 -1.92 g / cm 3 , and then adding the first glue to obtain the first mixture with the above specific gravity.

[0027] The specific gravity of the slurry containing the glaze is 1.41 g / cm 3 -1.43 g / cm 3 , applied at 425 g / m 2 -445g / m 2 The slurry comprising the topcoat is applied by spraying.

[0028] The highest temperature of the above-mentioned firing is 1160 ℃-1200 ℃, and the time is 35 min-55 min.

[0029] The above ranges are all optimal implementation range values. If the specific gravity is too high, the solid content is too high, and if the specific gravity is too low, the water content is too high, both of which will have an adverse effect on the final effect; and if the application amount is too high, it will increase the cost, and if it is too low, it will have an adverse effect on the final effect.

[0030] In some preferred implementations, three layers of the positioning glue are printed through three channels, and the grayscale of each channel is ≥85 and ≤95, preferably 90 (i.e., the three channels are 90-90-90 respectively), so as to increase the amount of glue to increase the viscosity, so that the dry granular mixture can be densely distributed and adhere more firmly, avoiding the positioning pattern effect affected by insufficient adhesion strength. After applying the dry granular mixture, the excess dry granular mixture that is not adhered to the positioning glue is removed (by suction) and can be used for recycling.

[0031] In some preferred implementations, when applying the above-mentioned dry granular mixture, a 40-mesh two-layer screen is used to apply the above-mentioned dry granular mixture. Due to the specific differentiation of the colorful dry granules and the transparent dry granules in the above-mentioned dry granular mixture, when applying the 40-mesh two-layer screen, the particle layout can be further optimized to achieve the above-mentioned effect (in the process of tumbling and falling, the colorful dry granules have a larger particle size, and when they collide with the mesh wall of the screen in the process of passing through the screen, they generate resistance and slow down the falling speed, while the transparent dry granules can quickly pass through the mesh holes of the screen due to their relatively small particle size and generate less kinetic energy, making it easier to adhere to the lower layer, which can effectively support the colorful dry granules and fill between the colorful dry granules, so that the colorful dry granules can be suspended in the transparent dry granules, which can further enhance the three-dimensional effect).

[0032] The beneficial effects of the present invention are as follows: the ceramic tiles prepared by the present invention have a three-dimensional suspended state with gorgeous and colorful effects, and have a smooth surface, strong transparency, good anti-fouling and wear resistance, and can meet the personalized aesthetic needs of consumers. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 Shown is a physical picture of the ceramic tile prepared in Example 1;

[0034] Figure 2 Shown Figure 1 A partial enlarged view of position a in the middle;

[0035] Figure 3 Shown is a physical picture of the ceramic tile prepared in Example 2;

[0036] Figure 4 Shown is a physical picture of the ceramic tile obtained in Example 3;

[0037] Figure 5 Shown is a physical picture of the ceramic tile obtained in Example 4;

[0038] Figure 6 Shown is a physical picture of the ceramic tile obtained in Example 5;

[0039] Figure 7 Shown is a physical picture of the ceramic tile prepared in Comparative Example 8;

[0040] Figure 8 Shown Figure 7 A local enlarged view of the position d in the middle;

[0041] Fig. 9 Shown is a physical picture of the ceramic tile prepared in Comparative Example 9;

[0042] Fig.10 Shown Fig. 9 A partial enlarged view of position e in the middle. DETAILED DESCRIPTION

[0043] The following will be combined with the embodiments and drawings to clearly and completely describe the concept and technical effects of the present invention, so as to fully understand the purpose, scheme and effect of the present invention. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.

[0044] Example 1

[0045] A colorful effect ceramic tile comprises, from bottom to top, a body layer, a glaze layer, a pattern layer, a dry particle mixture layer, a first protective glaze layer, a transparent dry particle layer and a second protective glaze layer.

[0046] The dry granule mixture layer is formed by a dry granule mixture, and the dry granule mixture includes colorful dry granules and transparent dry granules in a mass ratio of 1:0.6; the D97 of the colorful dry granules is 250 µm-300 µm, and the D97 of the transparent dry granules is 125 µm-150 µm;

[0047] The colorful dry particles are obtained by crushing zircon, and the colorful dry particles include SiO2 33%, ZrO2 67% by mass percentage.

[0048] The transparent dry particles include, by mass percentage, 56.5% SiO2, 7.8% Al2O3, 12.5% ​​CaO, 5.8% K2O, 2.5% Na2O, 14.5% ZnO, and the rest are loss on ignition and impurities; the raw materials of the transparent dry particles include, by weight, 23 parts of albite, 28 parts of quartz, 15.5 parts of calcite, 10 parts of wollastonite, 14.5 parts of zinc oxide, 3 parts of aluminum oxide, and 6 parts of potassium nitrate; the preparation method of the transparent dry particles includes the following steps: mixing the raw materials of the transparent dry particles, calcining and melting at 1400°C to obtain a glass melt, cooling the molten glass with a water-cooled metal roller, and crushing it to obtain the transparent dry particles.

[0049] The transparent dry particle layer is formed by transparent dry particles; the glaze layer is formed by a slurry containing glaze (Guangdong Dow Technology Co., Ltd.; GYS-MY13 glaze (powder)); the preparation method of the slurry containing the glaze includes the following steps: by weight, 100 parts of glaze, 13 parts of zirconium silicate, 40 parts of water, 0.2 parts of methyl cellulose and 0.35 parts of sodium tripolyphosphate are mixed and ball-milled, sieved and aged to obtain a slurry containing the glaze; the pattern layer is formed by spraying a preset pattern.

[0050] The first protective glaze layer and the second protective glaze layer are both formed by a first mixture, the first mixture includes a first glue (Foshan Sanshui Taiyang New Materials Co., Ltd., glue model: W-19) and a slurry, the slurry includes a protective glaze; the D97 of the protective glaze is 21 µm-25 µm; the protective glaze includes, by mass percentage: SiO2 56.7%, Al2O3 13.87%, CaO 10.23%, K2O 5.6%, Na2O 1.68%, ZnO 3.82%, and the rest is ignition loss and impurities. The raw materials of the protective glaze include, by weight: 46 parts of potassium feldspar, 18 parts of quartz, 16 parts of wollastonite, 10 parts of calcite, 7 parts of aluminum oxide, and 3 parts of zinc oxide. The preparation method of the slurry includes the following steps: mixing the raw materials of the protective glaze, water, a thickener (methyl cellulose) and a dispersant (sodium tripolyphosphate), and obtaining the slurry through ball milling, sieving and aging.

[0051] The method for preparing the colorful effect ceramic tile of this embodiment comprises the following steps:

[0052] (1) Obtaining a green body layer with a moisture content of less than 0.3% by mass;

[0053] (2) Spraying a slurry containing a glaze on the surface of the body layer; the specific gravity of the slurry containing a glaze is 1.42 g / cm 3 , applied at 435 g / m 2 ;

[0054] (3) Printing a preset pattern, and then printing positioning glue (Foshan Yidajia Precision Ceramics Technology Co., Ltd., glue model: CIK-AD1109) at the preset position; when printing the positioning glue, three channels are used for printing (i.e., three layers of glue are printed), and the printing grayscale is 90, i.e., 90-90-90;

[0055] (4) Use a 40-mesh two-layer screen to apply the dry granular mixture, and then remove the excess (i.e., non-adherent) dry granular mixture by suction; the application rate of the dry granular mixture is 260 g / m 2 ;

[0056] (5) Spraying the first mixture for the first time; wherein the specific gravity of the first mixture is 1.1 g / cm 3 , spraying amount is 275g / m2 ;

[0057] (6) Applying transparent dry granules; the application amount of transparent dry granules is 735 g / m 2 ;

[0058] (7) Spraying the first mixture for the second time; wherein the specific gravity of the first mixture is 1.08 g / cm 3 , spraying amount is 185g / m 2 ;

[0059] (8) Firing at a maximum temperature of 1180°C and polishing and grinding the edges to obtain the colorful ceramic tile (such as Figure 1 and Figure 2 As shown; from the surface of the ceramic tile, the colorful dry particles distributed in the preset position occupy about 65% of the surface area of ​​the preset position).

[0060] Example 2

[0061] A colorful ceramic tile (such as Figure 3 As shown, from the perspective of the ceramic tile surface, the colorful dry particles distributed in the preset position occupy about 70% of the surface area of ​​the preset position, and the colorful dry particles in the area outside the preset position occupy about 28% of the surface area of ​​the area outside the preset position). The difference between this embodiment and embodiment 1 is that:

[0062] 1) The mass ratio of colorful dry granules to transparent dry granules is 1:0.65; the colorful dry granules include, by mass percentage: SiO2 31.0%, ZrO2 69.0%; the raw materials of transparent dry granules include, by weight: albite 24.5 parts, quartz 29.5 parts, calcite 14 parts, wollastonite 11 parts, zinc oxide 13 parts, aluminum oxide 2.5 parts, potassium nitrate 5.5 parts; the transparent dry granules include, by mass percentage: SiO2 59.37%, Al2O3 7.21%, CaO 11.82%, K2O 5.51%, Na2O 2.67%, ZnO 13.58%, and the rest are loss on ignition and impurities;

[0063] 2) The raw materials of the protective glaze include, by weight: 49 parts of potassium feldspar, 16.5 parts of quartz, 15 parts of wollastonite, 9 parts of calcite, 8 parts of aluminum oxide, and 2.5 parts of zinc oxide; the protective glaze includes, by mass percentage: SiO2 53.9%, Al2O3 15.01%, CaO 11.2%, K2O 6.05%, Na2O 1.47%, ZnO 3.5%, and the rest are ignition loss and impurities;

[0064] 3) After printing the pattern and the positioning glue at the preset position in step (4) of Example 1, the dry granular mixture is applied for the first time, wherein the amount of the dry granular mixture applied is 285 g / m 2Then, the excess dry granular mixture that is not attached to the positioning glue at the preset position is removed by suction, and then the dry granular mixture is applied again, wherein the application amount of the dry granular mixture is 110 g / m 2 ;

[0065] 4) The preset patterns for printing are different, and the corresponding positioning glue patterns are also adjusted accordingly;

[0066] The rest is the same as Example 1.

[0067] Example 3

[0068] A colorful ceramic tile (such as Figure 4 As shown, from the perspective of the ceramic tile surface, the colorful dry particles distributed in the preset position occupy about 55% of the surface area of ​​the preset position, and the colorful dry particles in the area outside the preset position occupy about 15% of the surface area of ​​the area outside the preset position). The difference between this embodiment and embodiment 1 is that:

[0069] 1) The mass ratio of colorful dry granules to transparent dry granules is 1:0.55; the colorful dry granules include, by mass percentage: SiO2 36.0%, ZrO2 64.0%; the raw materials of transparent dry granules include, by weight: albite 22 parts, quartz 25.5 parts, calcite 17 parts, wollastonite 9.5 parts, zinc oxide 16 parts, aluminum oxide 3.5 parts, potassium nitrate 6.5 parts; the transparent dry granules include, by mass percentage: SiO2 53.35%, Al2O3 8.34%, CaO 13.27%, K2O 6.16%, Na2O 2.27%, ZnO 14.18%, and the rest are loss on ignition and impurities;

[0070] 2) The raw materials of the protective glaze include, by weight: 43 parts of potassium feldspar, 19.5 parts of quartz, 17 parts of wollastonite, 11 parts of calcite, 6 parts of aluminum oxide, and 3.5 parts of zinc oxide; the protective glaze includes, by mass percentage: SiO2 59.78%, Al2O3 12.88%, CaO 9.23%, K2O 5.25%, Na2O 1.96%, ZnO 4.13%, and the rest are ignition loss and impurities;

[0071] 3) After printing the pattern and the positioning glue at the preset position in step (4) of Example 1, the dry granular mixture is applied for the first time, wherein the amount of the dry granular mixture applied is 215 g / m 2 Then, the excess dry granular mixture that is not attached to the positioning glue at the preset position is removed by suction, and then the positioning glue is sprayed on the area (position) outside the positioning glue at the preset position, and then the dry granular mixture is applied again, wherein the application amount of the dry granular mixture is 80 g / m 2 , and remove the excess dry granular mixture that is not adhered to the positioning glue and the surface of the preset position by suction;

[0072] 4) The preset patterns for printing are different, and the corresponding positioning glue patterns are also adjusted accordingly;

[0073] The rest is the same as Example 1.

[0074] Example 4

[0075] A colorful ceramic tile (such as Figure 5 As shown, from the perspective of the ceramic tile surface, the colorful dry particles distributed in the preset position occupy about 75% of the surface area of ​​the preset position, and the colorful dry particles in the area outside the preset position occupy about 12% of the surface area of ​​the area outside the preset position). The difference between this embodiment and embodiment 1 is that:

[0076] 1) After printing the pattern in step (4) of Example 1, the positioning glue is printed on the pattern surface in a spreading manner, and the dry granular mixture is applied to the preset position (using a carved roller or a carved belt), wherein the application amount of the dry granular mixture is 305 g / m 2 Then, the dry granular mixture is applied again, wherein the application amount of the dry granular mixture is 65 g / m 2 , and remove the excess dry granular mixture that is not adhered and on the preset position by suction;

[0077] 2) The preset patterns for printing are different;

[0078] The rest is the same as Example 1.

[0079] Example 5

[0080] A colorful ceramic tile (such as Figure 6 As shown, from the surface of the ceramic tile, the colorful dry particles occupy about 8% of the surface area of ​​the ceramic tile), which is different from Example 1 in that:

[0081] 1) After printing the pattern in step (4) of Example 1, directly apply the dry granular mixture to the pattern surface in a spreading manner, wherein the amount of the dry granular mixture applied is 45 g / m 2 ;

[0082] 2) The preset patterns for printing are different;

[0083] The rest is the same as Example 1.

[0084] Comparative Example 1

[0085] A ceramic tile, which is different from Example 1 in that: the raw materials of transparent dry particles include, by weight: 23 parts of albite, 26 parts of quartz, 21 parts of calcite, 8.5 parts of wollastonite, 14.5 parts of zinc oxide, 1 part of aluminum oxide, and 6 parts of potassium nitrate. The transparent dry particles include, by mass percentage: SiO2 55.23%, Al2O3 5.84%, CaO 15.79%, K2O 5.7%, Na2O 2.36%, ZnO 14.21%, and the rest are ignition loss and impurities.

[0086] The rest is the same as Example 1.

[0087] Comparative Example 2

[0088] A ceramic tile, which is different from Example 1 in that: the raw materials of transparent dry particles include, by weight, 24.5 parts of albite, 29 parts of quartz, 10 parts of calcite, 11 parts of wollastonite, 14.5 parts of zinc oxide, 5 parts of aluminum oxide, and 6 parts of potassium nitrate. The transparent dry particles include, by mass percentage, 57.15% of SiO2, 11.28% of Al2O3, 8.83% of CaO, 5.51% of K2O, 2.72% of Na2O, 13.96% of ZnO, and the rest are loss on ignition and impurities.

[0089] The rest is the same as Example 1.

[0090] Comparative Example 3

[0091] A ceramic tile, which is different from Example 1 in that: the raw materials of transparent dry particles include, by weight, 18 parts of albite, 29 parts of quartz, 16 parts of calcite, 10.5 parts of wollastonite, 14.5 parts of zinc oxide, 3 parts of aluminum oxide, and 9 parts of potassium nitrate. The transparent dry particles include, by mass percentage, 56.6% of SiO2, 7.55% of Al2O3, 12.67% of CaO, 7.43% of K2O, 1.53% of Na2O, 14.08% of ZnO, and the rest are loss on ignition and impurities.

[0092] The rest is the same as Example 1.

[0093] Comparative Example 4

[0094] A ceramic tile, which is different from Example 1 in that: the raw materials of transparent dry particles include, by weight: 28 parts of albite, 27 parts of quartz, 14.5 parts of calcite, 9.5 parts of wollastonite, 14.5 parts of zinc oxide, 3 parts of aluminum oxide, and 3.5 parts of potassium nitrate. The transparent dry particles include, by mass percentage: SiO2 56.31%, Al2O3 7.98%, CaO 12.32%, K2O 3.67%, Na2O 3.36%, ZnO 14.86%, and the rest are ignition loss and impurities.

[0095] The rest is the same as Example 1.

[0096] Comparative Example 5

[0097] A ceramic tile, which is different from Example 1 in that: the raw materials of transparent dry particles include, by weight: 23 parts of albite, 28 parts of quartz, 15.5 parts of calcite, 10 parts of wollastonite, 14.5 parts of barium oxide, 3 parts of aluminum oxide, and 6 parts of potassium nitrate. The transparent dry particles include, by mass percentage: SiO2 56.47%, Al2O3 7.78%, CaO 12.53%, K2O 5.78%, Na2O 2.52%, BaO 14.53%, and the rest are ignition loss and impurities.

[0098] The rest is the same as Example 1.

[0099] Comparative Example 6

[0100] A ceramic tile, which is different from Example 1 in that: the raw materials of the protective glaze include, by weight, 44 parts of potassium feldspar, 17.5 parts of quartz, 17.5 parts of wollastonite, 15 parts of calcite, 3 parts of aluminum oxide, and 3 parts of zinc oxide. The protective glaze includes, by mass percentage, SiO2 56.13%, Al2O3 9.89%, CaO 12.91%, K2O 5.43%, Na2O 1.72%, ZnO 3.8%, and the rest is ignition loss and impurities.

[0101] The rest is the same as Example 1.

[0102] Comparative Example 7

[0103] A ceramic tile, which is different from Example 1 in that: the raw materials of the protective glaze include, by weight, 47.5 parts of potassium feldspar, 19 parts of quartz, 14.5 parts of wollastonite, 5 parts of calcite, 11 parts of aluminum oxide, and 3 parts of zinc oxide. The protective glaze includes, by mass percentage, 57.2% of SiO2, 17.85% of Al2O3, 7.37% of CaO, 5.82% of K2O, 1.63% of Na2O, 3.76% of ZnO, and the rest are ignition loss and impurities.

[0104] The rest is the same as Example 1.

[0105] Comparative Example 8

[0106] A ceramic tile (such as Figure 7 and Figure 8 As shown, from the surface of the ceramic tile, the colorful dry particles distributed in the preset position occupy an area of ​​>90% of the surface of the preset position), which differs from Example 1 in that: in the dry particle mixture, the mass ratio of the colorful dry particles to the transparent dry particles is 1:0.15.

[0107] The rest is the same as Example 1.

[0108] Comparative Example 9

[0109] A ceramic tile (such as Fig. 9 and Fig.10 As shown, from the perspective of the ceramic tile surface, the colorful dry particles distributed in the preset position occupy an area of ​​less than 20% of the surface of the preset position). The difference from Example 1 is that in the dry particle mixture, the mass ratio of the colorful dry particles to the transparent dry particles is 1:2.5.

[0110] The rest is the same as Example 1.

[0111] Comparative Example 10

[0112] A ceramic tile, which is different from Example 1 in that D97 of the transparent dry particles is greater than 155 μm.

[0113] The rest is the same as Example 1.

[0114] Comparative Example 11

[0115] A ceramic tile, which is different from Example 1 in that: D97 of the transparent dry particles is less than 120 μm.

[0116] The rest is the same as Example 1.

[0117] Comparative Example 12

[0118] A ceramic tile, which is different from Example 1 in that: D97 of the protective glaze is greater than 26 μm.

[0119] The rest is the same as Example 1.

[0120] Comparative Example 13

[0121] A ceramic tile, which is different from the embodiment 1 in that the D97 of the protective glaze is less than 20 μm.

[0122] The rest is the same as Example 1.

[0123] Comparative Example 14

[0124] A ceramic tile, which is different from Example 1 in that: no first protective glaze layer is provided, that is, after applying the dry particle mixture, the first mixture is not sprayed but transparent dry particles are directly applied.

[0125] The rest is the same as Example 1.

[0126] Comparative Example 15

[0127] A ceramic tile, which is different from the embodiment 1 in that no second protective glaze layer is provided, that is, after applying the transparent dry particles, no second spraying of the first mixture is performed but the ceramic tile is directly fired.

[0128] The rest is the same as Example 1.

[0129] Comparative Example 16

[0130] A ceramic tile, which differs from Example 1 in that: the first mixture does not include the first glue, and the slurry containing the protective glaze is directly sprayed twice according to the parameter conditions of Example 1.

[0131] The rest is the same as Example 1.

[0132] Performance test

[0133] The ceramic tiles of Examples 1-5 and Comparative Examples 1-16 were subjected to performance tests, specifically including wear resistance, stain resistance and surface quality tests. The surface wear resistance was tested using the method in GB / T3810.7, and the surface stain resistance and surface quality were tested using the method in GB / T3810.14-2016. The specific test results are shown in Table 1 below.

[0134] Table 1

[0135]

[0136]

[0137] It can be seen from the test data in Table 1 above that the colorful ceramic tiles prepared by the technical solution of the present invention have good wear resistance (up to level 4) and stain resistance (up to level 5), strong transparency, and the colorful dry particles have a three-dimensional suspension effect and a dazzling flashing effect, good color, good brick shape, and excellent quality.

[0138] In combination with Example 1, Comparative Examples 1-2 and Table 1, it can be seen that when the aluminum oxide content in the transparent dry particles is low and the calcium oxide content is high, the firing temperature is low, resulting in premature melting of the transparent dry particles, and it is also easy to crystallize and the permeability is poor; when the aluminum oxide content in the transparent dry particles is high and the calcium oxide content is low, the firing temperature is high, resulting in a decrease in glossiness, poor permeability, and low density, which makes the anti-fouling worse.

[0139] In combination with Example 1, Comparative Examples 3-4 and Table 1, it can be seen that when the potassium oxide content in the transparent dry particles is high and the sodium oxide content is low, crystallization will occur due to low surface tension; when the potassium oxide content in the transparent dry particles is low and the sodium oxide content is high, the surface tension will be large and the bubbles in the layer cannot be effectively discharged.

[0140] In combination with Example 1, Comparative Example 5 and Table 1, it can be seen that when the zinc oxide in the raw material of the transparent dry particles is replaced with barium oxide, the thermal expansion coefficient of the glass phase in the layer is increased, the chemical stability is deteriorated, and it is easy to combine with aluminum oxide and silicon oxide to form a barium oxide-aluminum oxide-silicon oxide crystallization phase to form crystallization, resulting in poor permeability.

[0141] In combination with Example 1, Comparative Examples 6-7 and Table 1, it can be seen that when the aluminum oxide content in the protective glaze is low and the calcium oxide content is high, the firing temperature is low, and at the same time, the transparent dry particles are further melted prematurely. The low-temperature melting is easy to crystallize in the later heat preservation and the permeability is deteriorated; when the aluminum oxide content in the protective glaze is high and the calcium oxide content is low, the firing temperature, surface tension and viscosity are increased, which is not conducive to the gas discharge during the reaction process, bubbles are prone to occur, the glossiness decreases, the sense of transparency deteriorates, and the density becomes low, which makes the anti-fouling and wear resistance worse.

[0142] In combination with Example 1, Comparative Examples 8-9 and Table 1, it can be seen that when the proportion of transparent dry particles in the dry particle mixture is small, that is, the colorful dry particles that account for a larger proportion are easy to stack on each other and there are empty (gap) gaps. Under the same firing conditions, due to the high melting point of the colorful dry particles and the low melting point characteristics of the transparent dry particles, the transparent dry particles cannot completely fill the gaps between the colorful dry particles when they are melted, which easily forms pores and glaze bubble defects. After polishing, the pores are exposed, resulting in poor anti-fouling and poor flatness; when the proportion of transparent dry particles in the dry particle mixture is large, and the colorful dry particles are too few, the three-dimensional suspended visual colorful effect presented by the colorful dry particles is not obvious, so that the realistic positioning grain effect in high-end stone cannot be imitated, and the visual perception and sense of grade are poor.

[0143] Combining Example 1, Comparative Examples 10-11 and Table 1, it can be seen that when the particle size of the transparent dry particles in the dry particle mixture is too large (under the premise of unchanged weight, the particle amount of the transparent dry particles is correspondingly reduced), it cannot completely fill the gaps between the colorful dry particles, so that pores and glaze bubbles are easily formed, resulting in poor anti-fouling; and when the particle size of the transparent dry particles as the surface layer is too large, the particle size distribution span becomes larger accordingly, making the surface rougher and the surface flatness worse (the polishing depth needs to be increased to solve this problem, but it is easy to cause the colorful dry particles to be The transparent dry particles in the dry granular mixture are too small (under the premise of unchanged weight, the amount of transparent dry particles increases accordingly), which is easier to settle in the bottom gap, making it easier for the colorful dry particles to float on the upper layer and aggregate, resulting in voids, which easily form pores and glaze bubble defects, resulting in poor anti-fouling; and the transparent dry particles as the surface layer have a smaller particle size, and the corresponding particle size distribution span is too small, which makes the transparent dry particles melt and level more quickly and easily flow out of the surface layer, resulting in an uneven surface.

[0144] In combination with Example 1, Comparative Examples 12-13 and Table 1, it can be seen that when the particle size of the protective glaze is too large, the coupling effect between the protective glaze and the dry particle mixture is not good during the first layer spraying process, thereby insufficiently protecting the pattern layer and the colorful dry particles, resulting in poor pattern color; and after the second layer is sprayed, the bonding with the first layer of the protective glaze is not thorough, and the low-temperature eutectic with the transparent dry particles is not good, and the permeability becomes poor; when the particle size of the protective glaze is too small, although the protection of the pattern layer and the colorful dry particles is better, when it is used as a surface layer with the transparent dry particles, the too fine particle size will melt faster, resulting in poor melting matching with the transparent dry particles, resulting in poor surface flatness, poor anti-fouling and wear resistance.

[0145] In combination with Example 1, Comparative Examples 14-15 and Table 1, it can be seen that when the first protective glaze is not sprayed on the dry particle mixture layer, but transparent dry particles are directly applied thereon, the upper layer of the dry particle mixture may not be firmly adhered due to the lack of protection of the protective glaze containing glue, and may scatter, resulting in poor positioning (matching with the pattern) accuracy, and also causing the gaps between the coarser particle size (D97 is 250µm-300µm) of the colorful dry particles in the dry particle mixture and the inkjet pattern to form ink dots, thereby affecting the pattern effect; when the surface of the transparent dry particle layer is When the second protective glaze is not sprayed, the transparent dry particles can be easily blown away by the fan before entering the kiln for firing, affecting the surface flatness (because any ceramic tile product is equipped with a fan when entering the kiln before firing, that is, the surface is blown to prevent dirt from falling and causing surface quality problems of the product). In addition, due to the use of a single transparent dry particle surface layer, the gaps between the dry particles lead to poor surface bonding, making the surface of the ceramic tile after firing generally transparent, poorly fused, and poorly flat (the polishing depth needs to be increased to solve this problem, but it is easy to cause colorful dry particles to protrude from the surface), and poor anti-fouling and wear resistance.

[0146] In combination with Example 1, Comparative Example 16 and Table 1, it can be seen that when the protective glaze does not contain glue, the upper layer of the dry particle mixture may not adhere firmly and may scatter, resulting in poor positioning (matching with the pattern) accuracy, while the transparent dry particles on the surface can be easily blown away by the fan before entering the kiln for firing, affecting the surface flatness (because any tile product is equipped with a fan when entering the kiln before firing, that is, the surface is blown to prevent dirt from causing surface quality problems of the product).

[0147] It can be seen that the ceramic tiles produced in the embodiment of the present scheme can show the three-dimensional suspended visual colorful effect of the colorful dry particles at different angles under the irradiation of light, and due to multiple reflections and refractions, each surface of the colorful dry particles presents a variety of different luster flashes, which solves the problem of the grain effect of the prior art in imitating high-end stone that is not realistic enough, and brings new visual perception and higher-end use enjoyment to consumers.

[0148] The above is only a preferred embodiment of the present invention. The present invention is not limited to the above implementation. As long as the technical effect of the present invention is achieved by the same means, it should belong to the protection scope of the present invention. Within the protection scope of the present invention, its technical scheme and / or implementation method can have various modifications and changes.

Claims

1. A colorful ceramic tile, characterized in that: From bottom to top, it includes a body layer, a glaze layer, a pattern layer, a dry particle mixture layer, a first protective glaze layer, a transparent dry particle layer, and a second protective glaze layer; The dry granule mixture layer is formed by a dry granule mixture, wherein the dry granule mixture comprises colorful dry granules and transparent dry granules in a mass ratio of 1:(0.55-0.65); the D97 of the colorful dry granules is 250 µm-300 µm, and the D97 of the transparent dry granules is 125 µm-150 µm; The colorful dry particles include, by mass percentage: SiO2 31.0%-35.0%, ZrO2 65.0%-69.0%; The transparent dry particles include, by mass percentage, SiO2 53.0%-60.0%, Al2O3 7.2%-8.4%, CaO11.5%-13.5%, K2O 5.3%-6.3%, Na2O 2.2%-2.8%, ZnO 13.5%-15.5%, and the rest are loss on ignition and impurities; The transparent dry particle layer is formed by the transparent dry particles; The first protective glaze layer and the second protective glaze layer are both formed by a first mixture, the first mixture includes a first glue and a slurry, the slurry includes a protective glaze; the D97 of the protective glaze is 21 µm-25 µm; the protective glaze includes, by mass percentage, SiO2 53.3%-60.0%, Al2O3 12.5%-15.3%, CaO 9.0%-11.4%, K2O 5.0%-6.2%, Na2O 1.4%-2.0%, ZnO 3.4%-4.2%, and the rest are ignition loss and impurities.

2. The colorful effect ceramic tile according to claim 1, characterized in that: The raw materials of the transparent dry particles include, by weight: 21-25 parts of albite, 25.5-30.5 parts of quartz, 14-17 parts of calcite, 9-11 parts of wollastonite, 13-16 parts of zinc oxide, 2.5-3.5 parts of aluminum oxide, and 5.5-6.5 parts of potassium nitrate.

3. The colorful effect ceramic tile according to claim 2, characterized in that: The preparation method of the transparent dry particles comprises the following steps: mixing the raw materials of the transparent dry particles, calcining and melting them, cooling them and crushing them to obtain the transparent dry particles.

4. The colorful effect ceramic tile according to claim 1, characterized in that: The raw materials of the protective glaze include, by weight: 42-50 parts of potassium feldspar, 16-20 parts of quartz, 14.5-17.5 parts of wollastonite, 9-11 parts of calcite, 6-8 parts of aluminum oxide, and 2.5-3.5 parts of zinc oxide.

5. The colorful effect ceramic tile according to claim 4, characterized in that: The preparation method of the slurry comprises the following steps: mixing the raw materials of the protective glaze, water, a thickener and a dispersant, and obtaining the slurry through ball milling, sieving and aging.

6. A method for preparing a colorful effect ceramic tile according to any one of claims 1 to 5, characterized in that: The following steps are involved: Applying a slurry containing a glaze on the surface of the green body layer, followed by spraying and applying, then spraying the first mixture for the first time, then applying the transparent dry particles, and then spraying the first mixture for the second time; firing to obtain the colorful ceramic tile; The specific process of the printing and application treatment includes scheme 1, scheme 2, scheme 3, scheme 4 or scheme 5; the scheme 1 includes the following steps: printing a pattern to form the pattern layer, and then applying the dry granular mixture, the application amount is 20g / m 2 -120 g / m 2 ; The second scheme comprises the following steps: printing a pattern to form the pattern layer, printing a positioning glue on the surface of the pattern layer according to a preset position, and then applying the dry granular mixture, and then removing the excess dry granular mixture that is not attached to the positioning glue, and the application amount is 200 g / m 2 -320 g / m 2 ; The third scheme comprises the following steps: printing a pattern to form the pattern layer, printing positioning glue on the surface of the pattern layer according to a preset position, and then applying the dry granular mixture for the first time, with an application amount of 200 g / m 2 -320 g / m 2 Then, the excess dry granular mixture that is not attached to the positioning glue is removed, and then the dry granular mixture is applied for the second time, with an application amount of 20 g / m 2 -120 g / m 2 ; The fourth scheme comprises the following steps: printing a pattern to form the pattern layer, printing positioning glue on the surface of the pattern layer according to a preset position, and then applying the dry granular mixture for the first time, with an application amount of 200 g / m 2 -320 g / m 2 Then, the excess dry granular mixture that is not adhered to the positioning glue is removed, and then the positioning glue is sprayed at a non-preset position, and then the dry granular mixture is applied for the second time, with an application amount of 20 g / m 2 -120 g / m 2 , and then removing the excess dry granular mixture that is not adhered to the positioning glue; The fifth scheme comprises the following steps: printing a pattern to form the pattern layer, printing positioning glue on the surface of the pattern layer to cover the pattern layer, and applying the dry granular mixture at a preset position in an amount of 200 g / m 2 -320 g / m 2 Then the dry granular mixture is applied again at an application rate of 20 g / m 2 -120 g / m 2 , and then remove the excess dry granular mixture that is not adhered to the preset position.

7. The preparation method according to claim 6, characterized in that: The amount of transparent dry particles applied is 725 g / m 2 -745 g / m 2 ; and / or, during the first spraying, the specific gravity of the first mixture is 1.09 g / cm 3 -1.11 g / cm 3 , spraying rate is 265 g / m 2 -285 g / m 2 ; and / or, during the second spraying, the specific gravity of the first mixture is 1.07 g / cm 3 -1.09 g / cm 3 , spraying rate is 175 g / m 2 -195 g / m 2 .

8. The preparation method according to claim 6, characterized in that: The specific gravity of the slurry containing the glaze is 1.41 g / cm 3 -1.43 g / cm 3 , applied at 425 g / m 2 -445 g / m 2 .

9. The preparation method according to claim 6, characterized in that: When the specific process of the printing and dispensing treatment is the second, third, fourth or fifth scheme, three layers of the positioning glue are printed, and the printing grayscale is ≥85 and ≤95.

10. The preparation method according to claim 6, characterized in that: The dry granular mixture is applied using a 40-mesh two-layer screen.

Citation Information

Patent Citations

  • Ceramic tile with positioning crystal flash effect and preparation method of ceramic tile

    CN113045202A

  • Ceramic dry granular glaze, crystal diamond flash ceramic tile and preparation methods of ceramic dry granular glaze and crystal diamond flash ceramic tile

    CN113788620A